2012
DOI: 10.1111/jwip.12000
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Demographic and Technical Profile on Success of Independent Inventors in Sri Lanka

Abstract: The remarkable growth of patent applications in Asia has been the central focus of the recent studies on technological knowledge creation. However, all the Asian countries have not shown similar growth and hence, have not gained similar academic attention. Especially, the lower and middle‐income countries in South Asia are stagnating in technological knowledge creation. Sri Lanka is one such country that has high proportion of independent inventors in their innovation system. Owing to small number of inventors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The majority of studies undertaken on ownership of innovation and new technology focus on a single category of ownership and are based on Institutes of Higher Learning (Jensen & Thursby, 2001;Mazzoleni & Nelson, 2005;Crespi, Geuna, & Verspagen, 2006) or Government Research Institutes (GRI's) or based on commercial firms (Cohen, Nelson, & Walsh, 2000;Landabaso, Oughton, & Morgan, 2001). Fewer studies track the commercial success of independent inventors (Svensson, 2012;Wickramasinghe & Ahmad, 2011, Wilkins, Remias, & Kharoujik, 2008Weick & Eakin, 2005). Therefore, there exists a scarcity of study that explores divergent patent ownership in a single study on a national scale that includes different types of patent ownership ranging from independent inventors, academic researchers and those inventors and researchers employed by a commercial enterprise.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies undertaken on ownership of innovation and new technology focus on a single category of ownership and are based on Institutes of Higher Learning (Jensen & Thursby, 2001;Mazzoleni & Nelson, 2005;Crespi, Geuna, & Verspagen, 2006) or Government Research Institutes (GRI's) or based on commercial firms (Cohen, Nelson, & Walsh, 2000;Landabaso, Oughton, & Morgan, 2001). Fewer studies track the commercial success of independent inventors (Svensson, 2012;Wickramasinghe & Ahmad, 2011, Wilkins, Remias, & Kharoujik, 2008Weick & Eakin, 2005). Therefore, there exists a scarcity of study that explores divergent patent ownership in a single study on a national scale that includes different types of patent ownership ranging from independent inventors, academic researchers and those inventors and researchers employed by a commercial enterprise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past studies have found that while IHL and GRI's preferred method of commercialising was through licensing, individually owned patents were commercialised most often through start-ups as they preferred to retain ownership than to license as it offered more control (Wilkins, Remias, & Kharoujik, 2008). A further reason for poor commercial success has been attributed to patented technology by independent inventors being classified as low technology (Weick & Eakin, 2005;Wickramasinghe & Ahmad, 2011) or being too embryonic compared with inventions arising from academic research or by a commercial enterprise. Patent law permits patent filing at the early stages of the innovation process, at which time the patented invention may be prematurely embryonic.…”
Section: Introductionmentioning
confidence: 99%
“…The inventions developed by the scientific community failed to impact commercial products by lack of technology transfers to commercial enterprise. Therefore, the non-achievement of commercialisation of most patented innovations is a pressing problem for the country (Wickramasinghe & Ahmad, 2012). The non-achievement of commercialisation attributes to R&D undertaken by academia misaligned with industry needs in terms of identifying market requirements and a lack of understanding between the scientific community and the business community (Innovation and Entrepreneurship Strategy for Sri Lanka 2018 -2022).…”
Section: Given the Significance Of Commercialisation It Is Crucial To Understand What Factors Determine An Invention's Commercial Successmentioning
confidence: 99%
“…Results of many studies reveal that to achieve high innovation capability; organisations first need to develop the behavioural and cultural context and practices for shaping an innovative culture. Further (Wickramasinghe & Ahmad, 2012) recommend the research requirements to conduct more relational studies to understand the influences of demographic, technical, psychological and social factors on the innovation process activities of the local innovation systems in Sri Lanka. In this context, the policymakers and the decision makers in Sri Lanka should take serious notes to bring the industries and to guide them to capture the expected opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore to understand the current status and to suggest an improvement, the study on innovation in Sri Lankan context is required. Further (Wickramasinghe & Ahmad, 2012) suggest more relational studies to understand the influences of demographic, technical, psychological and social factors on the innovation process activities of the local innovations in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%